(untitled) (Fiep Bulletin - online, 2011)
Continued formation of professors is, nowadays, a basic guideline of the Ministry of Education of Brazil and other managing agencies of the national education. In such a way, proposals in this sense have been understood as basic and necessary to subsidize the practice of the professors. This study started from the observation that Physical Education professionals working in schools need a continuous process of formation to be in accordance to the current demands of Physical Education in schools. The aim of this study was to verify the benefits of a continued formation on pedagogical practice of these professinals. Data was collected in 10 public schools of state of Rio de Janeiro. Questionnaire was composed by closed and opened questions (when they were asked for some explanation on the alternatives chosen). The conclusion was that continued formation was directly related to the preparation for public contests, which may lead to the interpretation that there is a trend among these professionals to acquire a secure financial support with public jobs. According to Molina and Devis, continued formation should be carried on from the pedagogical practice itself as a means of knowledge and not in preparatory courses that teach and explain how things should be done. It is recommended that a research be carried through comparing the speech of the professors with their practice, so that a better conclusion could be reached about the participation in preparatory courses as a form of continued formation which could make it possible to the professor to develop his practice in accordance to the current demands of Physical Education in schools.